Physicochemical properties of binder gel in alkali-activated fly ash/slag exposed to high temperatures. (November 2016) - Park, S.M.; Jang, J.G.; Lee, N.K.; Lee, H.K.
Abstract: The present study investigated the physicochemical properties of binder gel in alkali-activated fly ash/slag exposed to high temperatures. Strength test results showed that the strength increased until exposure to 400 °C and thereafter started to decrease. The strength increase below 400 °C was attributed to the binder gel which formed after exposure, decreasing the porosity. The dehydration of C-A-S-H and the formation of N-A-S-H simultaneously occurred, inducing the transformation of pore structure from microporous to mesoporous state. The crystallization of the binder gel resulted in an increase in the porosity, thereby inducing a decrease in the strength above 400 °C and is responsible for the transformation of the pore structure from mesoporous to macroporous state. The porosity under high temperatures had an inverse relationship with the strength, and was significantly altered as the binder gel underwent additional formation, dehydration and crystallization.